Correlation–aware multipath selection to enhance path diversity in ubiquitous computing environment. (27th November 2012) - Wang, Jingyu; Liao, Jianxin; Li, Tonghong; Zhang, Ping
Different paths are likely to overlap each other and even share bottleneck, which can weaken the path diversity gained through Concurrent Multipath Transfer (CMT). Spurred by this observation, it is necessary to select a limited number of independent paths as much as possible, so we fall back on end–to–end probes to estimate path correlation. This paper focuses on a new topic of correlation–aware multipath selection, with formal and systematic problem definition, modeling and solution. Based on well–designed multipath delay probing, a Grouping–based Multipath Selection (GMS) mechanism is developed to avoid shared bottleneck between topologically joint paths.